Function and expression of sulfonylurea, adrenergic, and glucagon‐like peptide 1 receptors in isolated porcine islets. (7th May 2014) - Kelly, Amy C.; Steyn, Leah V.; Kitzmann, Jenna P.; Anderson, Miranda J.; Mueller, Kate R.; Hart, Nathaniel J.; Lynch, Ronald M.; Papas, Klearchos K.; Limesand, Sean W.
Abstract The scarcity of human cadaveric pancreata limits large‐scale application of islet transplantation for patients with diabetes. Islets isolated from pathogen‐free pigs provide an economical and abundant alternative source assuming immunologic barriers are appropriate. Membrane receptors involved in insulin secretion that also have potential as imaging targets were investigated in isolated porcine islets. Quantitative (q)PCR revealed that porcine islets express mRNA transcripts for sulfonylurea receptor 1 (Sur1), inward rectifying potassium channel (Kir6.2, associated with Sur1), glucagon‐like peptide 1 receptor (GLP1R), and adrenergic receptor alpha 2A (ADRα2A). Receptor function was assessed in static incubations with stimulatory glucose concentrations, and in the presence of receptor agonists. Glibenclamide, an anti‐diabetic sulfonylurea, and exendin‐4, a GLP‐1 mimetic, potentiated glucose‐stimulated insulin secretion >2‐fold. Conversely, epinephrine maximally reduced insulin secretion 72 ± 9% (P < 0.05) and had a half maximal inhibitory concentration of 60 nm in porcine islets (95% confidence interval of 45–830 nm). The epinephrine action was inhibited by the ADRα2A antagonist yohimbine. Our findings demonstrate that porcine islets express and are responsive to both stimulatory and inhibitory membrane localized receptors, which can be used as imaging targets after transplantation or to modify insulin secretion.